Aerosol single‐scattering albedo over the global oceans: Comparing PARASOL retrievals with AERONET, OMI, and AeroCom models estimates. Issue 18 (30th September 2015) - Lacagnina, Carlo; Hasekamp, Otto P.; Bian, Huisheng; Curci, Gabriele; Myhre, Gunnar; van Noije, Twan; Schulz, Michael; Skeie, Ragnhild B.; Takemura, Toshihiko; Zhang, Kai
Abstract: The aerosol single‐scattering albedo (SSA) over the global ocean is evaluated based on polarimetric measurements by the PARASOL (Polarization and Anisotropy of Reflectances for Atmospheric Sciences coupled with Observations from a Lidar) satellite. For the first time, global ocean SSA and Absorption Aerosol Optical Depth (AAOD) from this instrument are shown and evaluated against other observations (the Aerosol Robotic Network, AERONET, and the Ozone Monitoring Instrument, OMI). The observational data sets compare reasonably well, with the majority of the colocated points within 0.05 of the AERONET measurements. PARASOL shows that SSA is characterized by high spatial and seasonal variability, also over the open ocean far from the inland emission regions. The near global coverage in the visible spectral range provided by the PARASOL retrievals represents a unique opportunity to evaluate aerosol optical properties simulated by global aerosol models, as performed in the Aerosol Comparisons between Observations and Models (AeroCom) framework. The SSA (AAOD) estimated by the AeroCom models is generally higher (smaller) than the SSA (AAOD) retrieved from PARASOL. On the other hand, the mean simulated aerosol optical depth is consistent or slightly underestimated compared with observations. An overestimate of the aerosol scattering, compared to absorption, by the models would suggest that these simulate an overly strong aerosol radiative cooling at top of atmosphere, over most of the ocean surfaces. This implies that aerosols have a potentially stronger direct and semidirect impact within the atmosphere than currently simulated. Key Points: First global ocean comparison of PARASOL SSA with observations and models PARASOL observes stronger aerosol absorption than models, larger in the tropics Direct aerosol radiative effect at TOA is overestimated by models